Surface Degradation and Chemical Electrolyte Oxidation Induced by the Oxygen Released from Layered Oxide Cathodes in Li−Ion Batteries. Issue 5 (25th March 2019) - Leanza, Daniela; Mirolo, Marta; Vaz, Carlos A. F.; Novák, Petr; El Kazzi, Mario
Abstract: High‐resolution, surface sensitive soft X‐ray photoemission electron microscopy (XPEEM) reveals the fine interplay between oxygen and transition metal (TM) redox activities on the surface of a Li1.17 (Ni0.22 Co0.12 Mn0.66 )0.83 O2 (Li‐rich NCM) electrode. We demonstrate that the oxidation of oxygen in the lattice is accompanied by TM reduction already at 4.47 V vs. Li + /Li, as a result of oxygen loss from the surface, the latter process being enhanced at 4.8 V where oxygen gas reaches a maximum release rate. Simultaneously, we find evidence for the chemical oxidation of the electrolyte solvents above 4.8 V induced by the released oxygen, leading to the formation of a carbonate by‐products layer that covers homogeneously the particles of the counter electrode Li4 Ti5 O12 (LTO). The latter observation demonstrates that migration‐diffusion of such oxidized solvent by‐products occurs only when the solvents are chemically oxidized. We showed also that the Li‐rich NCM is susceptible to oxygen loss during soaking in the electrolyte, which causes TMs reduction and the poisoning of the counter electrode. Abstract : Oxygen oxidation in the lattice of Li‐rich NCM (Ni, Co, Mn) electrodes leads to a surface that is poor in O species and rich in reduced transition metals (TMs). This reaction is enhanced above 4.8 V, where oxygen release reaches a maximum. The storage behavior of the cathode in the electrolyte is also susceptible to oxygen loss from the surface. Such parasitic reactions pollute the counter electrode with TMs and organic/inorganic species.